Effect of finerenone on urinary protein and inflammatory factor levels in type 2 diabetes mellitus patients with diabetic kidney disease - Jia Song; Yan Kang; Lina Wang; YuQing Guo; XinJu Jia; ShanShan Dong; Yimeng Li; Dan Wang; JingMin Gao; AiGe Yang (PLoS ONE, 2025)
Aims This study aimed to investigate the efficacy and safety of finerenone in the treatment of diabetic kidney disease (DKD) in the real-world medical setting and explore the underlying mechanism of its kidney-protecting effects from the perspective of the inflammatory response. Materials and Methods Forty-eight DKD patients were selected and completed a 6-month finerenone treatment. Renal parameters, inflammatory cytokines, other related indicators and adverse effects were collected at every visit. Additionally, subgroup analysis was conducted on the microalbuminuria group (baseline urinary albumin/creatinine ratio (UACR) 30 – < 300 mg/g) and the macroalbuminuria group (baseline UACR ≥ 300 mg/g). Results After finerenone treatment, the levels of UACR, urinary β2-microglobulin (β2-MG) and proinflammatory cytokines in patients decreased compared with the pretreatment levels. Moreover, the rates of decrease in the UACR levels in the macroalbuminuria group were significantly greater than those in the microalbuminuria group. In the initial stage of treatment, the patient’s estimated glomerular filtration rate (eGFR) level decreased and serum potassium level increased compared to before, but with prolongation of the treatment time, both eGFR and serum potassium levels remained stable. Conclusions With the assistance of RAS inhibitors, SGLT2 inhibitors, and GLP-1 receptor agonists, finerenone effectively reduces urinary protein and improves the inflammatory response, demonstrating relatively manageable safety in real-world DKD treatment. The patients with macroalbuminuria may experience greater benefits.